Specialised Environmental Courts as a Driver of Environmental Protection in South Africa - Olowa, Abimbola; Feris, Loretta (Southern African Public Law, 2025)
The judiciary plays a vital role in advancing environmental protection. This article critically examines three key roles played by the judiciary towards the achievement of environmental protection—the development of environmental jurisprudence through the interpretation and application of the substantive environment right, the enforcement of environmental laws and the promotion of compliance with environmental laws. It evaluates the extent to which general courts in South Africa have fulfilled these key roles and argues that specialised environmental courts are more appropriately positioned to execute these roles effectively. Using the Environment and Land Court of Kenya, the Land and Environment Court of New South Wales and Hermanus Environmental Court as case studies, it explores the potential benefits of specialised environmental courts in strengthening these roles in South Africa. The analysis underscores the contributions of these specialised environmental courts to the development of environmental jurisprudence and the advancement of environmental protection.